IMPLEMENTATION OF COMMUNITY EDUCATION PROGRAM BY POLDA RIAU IN 2017 - Dessy Anggraini; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Based on the instruction of Kapolri Juklak/05/V/2003 dated 29 May 2003 concerning public education in the field of traffic that the education Program undertaken by the police in Riau, among other school security patrol, Police Goes To School and Goes to Campus, Sahabat Anak Police and Police Goes To Community as well as unorganized communities conducted by Polda Riau but in reality there are still many violations that occur especially students and students who Aged 16-30 years. The purpose of this research is the first of how the implementation of public education Program by Riau Police in 2017. Second to know the factors that affect the implementation of community education Program by the Riau Polda year 2017. The concept of the theory used by the authors is the implementation of the researcher Program using qualitative research with descriptive study. In collecting data, authors use interviews and observation techniques. Authors use informant as information as a source in the validity of data. The results of this study showed that the implementation of community education Program by Polda Riau in 2017 is still not maximal, evidenced increasing each year casualty accident and traffic violations. Factors affecting the implementation of community education programs include communication, resources, disposition and bureaucratic structure. Keywords: Program implementation, community education